Insurance Regulation Updates in Facing Insurance Developments - Santri, Selvi Harvia; Erlina (Proceeding International Conference on Social Sciences, 2026)
The insurance business contributes to Indonesia's progress by protecting individuals and businesses from financial risks and channeling public funds into productive investments that support national economic growth. Insurance can provide a sense of security, enabling individuals and companies to operate more stably and boldly in taking business risks, while the collected funds are channeled into various investment instruments that stimulate economic development. Essentially, insurance is a financial service product that offers risk transfer services, so the main function of insurance is to transfer risk from the Insured to the Insurer. The current development of the insurance business brings significant changes that can bring innovation and convenience for consumers, but the development of the insurance world is not in line with existing regulations, which can give rise to problems in the future, so that the need for renewal of insurance regulations that govern the development of insurance. The purpose of this study is to determine insurance regulations in facing the development of insurance and to understand the development of insurance to the needs of the community. The type of research used is a juridical-normative with a legal history and legislation approach. The data used is secondary data. Qualitative methods are used to analyze and describe the data descriptively. The research results show that insurance regulations, in response to the development of insurance, still rely on existing insurance regulations, namely Insurance Law No. 40 of 2014 concerning Insurance Business and Financial Services Authority Regulation No. 13/POJK.02/2018 concerning Digital Financial Innovation, which regulates technology insurance. These regulations are still insufficient to regulate all insurance provisions adapted to business developments in Indonesia. The development of insurance to meet public needs can be seen in the increasing public interest in insurance.